The measurement of the economic, social and environmental impact of Peer to Peer online platforms: The case of collaborative consumption - Gordo López, Ángel; de Rivera, Javier; Cassidy, Paul R. (Empiria. Revista de metodología de ciencias sociales, 2020)
Over the last decade, the rise of peer-to-peer online markets has become a major sociocultural and economic phenomena and been described as a collaborative or sharing economy. However, understanding their impact has been mired in controversy and disagreement. Proponents of the sharing economy hail its potential to be a panacea for many of the world’s problems, but more critical perspectives point to research that undermines these claims. The rapid growth of this type of activity has placed public administrators in particular under pressure to develop appropriate policy and regulation. However, policy development is severely hindered by a lack of data and suitable measurement techniques. Work to develop appropriate data measurement tends to focus on economic measurement at the expense of social and environmental impact. This research paper seeks to contribute to understanding this problem area by taking a comprehensive triple impact perspective (economic, social and environmental) of the object of study. Employing a Delphi technique, the research developed forty-seven impact indicators across the three areas of measurement. A lo largo de la última década, el crecimiento de las plataformas de intercambio entre iguales, descritas como economía colaborativa, representó un de los fenónenos económicos y socio-culturales más importantes. Los defensores de la economía colaborativa resaltan su potencial para convertirse en la panacea de los grandes problemas mundiales, mientras que las perspectivas críticas apuntan a investigaciones que contradicen estas ideas. El rápido crecimiento de este tipo de actividad ha puesto a la administración pública bajo la presión de tener que desarrollar medidas de regulación adecuadas. Sin embargo, el desarrollo de regulación en este sentido adolece gravemente de la falta de datos y de técnicas adecuadas para medir el impacto. Los intentos por medir este impacto están por lo general concentrads en producir indicadores económicos, a expensas de la medición del impacto social y medioambiental. Esta investigación trata de contribuir a esta cuestión desde una perspectiva holística que estudia el triple impacto (económico, social y medioambiental) de este objeto de estudio. Recurriendo a un estudio Delphi esta investigación ha desarrollado 47 indicadores de impacto en estas tres aéreas de medición.